The prevalence of musculoskeletal disorders among computer related professionals of Dahod City, Gujarat: a cross sectional study - Kumar, Sanjay; Chinchodkar, Kishor N.; Bute, Jayashri (International Journal Of Community Medicine And Public Health, 2023)
Background: Use of any gadgets like Laptops/Desktops etc. on daily basis generates disorders in body. The term use to denote this disorder as ‘Musculoskeletal Disorder’ (MSD). Methods: Observational cross-sectional study was conducted by a random sampling method. A total 350 study subjects taken from Dahod city, Gujarat of various professionals like offices, institutions etc., who were working minimum one year with laptops/desktops at least four hours in a day with age 18-60 years. With the help of Neck Disability Index (NDI), Cornell Hand Discomfort Questionnaire (CHDQ) proforma data were collected. Descriptive statistics, Spearman’s correlation, Chi-square test and Binary logistic regression was used to find role of predictors with an increased risk of pain. Results: The mean±SD age of participants was 31.03±10.031 while males were higher than females (69.1% vs 30.9%). 53% subjects reported pain in hand, neck and/or back due to prolonged use of laptops/desktops. There exists positive correlation between NDI with CHDQ (r=0.57, p<0.001), significant association between working time (hours) and pain intensity (χ2=6.94, p<0.001). Computer use, age, gender, education were statistically significant predictors (p<0.05), with an increased risk of pain. Conclusions: The results of this study showed MSD at different areas of hand and neck, back site of the body. To prevent MSD’s some exercises, ideal posture at time of working on computers are recommended, for eye safety, professionals should regular check their eyes. Proper diet plan is proposed. With the help of these suggestions, one can increase work efficiency without MSD.